Fabrication of a novel nickel-nickel aluminate nanocomposite with improved nanoparticle dispersion. Issue 6 (15th March 2022) - Wang, Yulei; Ding, Youpeng; Hao, Ming; Fang, Baizeng; Li, Yang; Liang, Jinsheng; Gao, Peizhang; Wang, Fei
Abstract: The demand for nickel-based catalysts is increasing continuously owing to their low fabrication costs and relatively good performance. Nevertheless, nickel-based catalysts have some drawbacks mainly including poor nanoparticle dispersion of active components, low stability at high temperature, and short service life. In this study, novel nickel-nickel aluminate/sepiolite nanocomposites with spinel NiAl2 O4 as an intermediate transition layer were successfully synthesized through the reduction of the NiAl2 O4 /sepiolite composites obtained by a co-precipitation method. The optimal fabrication parameters of the NiAl2 O4 /sepiolite composite were determined to be 700 °C for the furnacing temperature, pH = 9 for the precursor suspension, 1:1 for the volume ratio of ethanol to deionized water, and a mass ratio of 7.5: 1 for metal salt/sepiolite. The spinel NiAl2 O4 nanoparticles of approximate 10 nm were uniformly dispersed on the sepiolite external surface. The most suitable reduction temperature for the formation of metallic Ni was measured to be 600 °C, and metallic Ni nanoparticles of about 5 nm were embedded in the NiAl2 O4 nanoparticles with a good dispersion during the reduction process. The present study is expected to offer a valid route for the synthesis of novel supported nickel-based catalysts with high nanoparticle dispersion at a low cost.